Valor nutricional do resíduo úmido de cervejaria in natura conservado sob condições aeróbias ou anaeróbias - Souza, Leiliane Cristine de (2010)
The high cost of feed for ruminants is a limiting factor for increasing productivity, boosting the search for alternative sources of food in order to minimize production costs. The brewery s waste (BW) deserves prominence in this situation, because it has high nutritional quality and great potential for livestock production. The BW is the result of the initial processing of the manufacture of beers, however the limitations to effective use of the RUC in animal feed are mainly related with storage and high humidity of the material, hindering the transport and storage. The ensiling of the BW is presented as an efficient alternative in the preservation of the material, paying attention to the quality of the material after the process of anaerobic fermentation. The nutritional evaluation of the BW is of fundamental importance for achieving efficiency in the diets, optimize productive performance and reduce costs. The aim of this study was to evaluate methods of conservation aerobic and anaerobic of brewery s waste, performing microbiological testing and evaluating the quality of silage fermentation, chemical composition, as well the digestibility in vitro and degradability in situ brewery s waste in natura and ensiled. The conservation of the brewery s waste packaged under aerobic conditions was not appropriate because the strong development of filamentous fungi and yeasts; however the storage under anaerobic conditions proved to be an efficient conservation process. The ensilage brewery s waste preserved nutritional quality of the material. The evaluation of chemical composition, in vitro digestibility and in situ degradability of in natura and ensiled BW showed that the material can be characterized as roughage feed with potential use in ruminant feed